Influencia del facebook en la creación de estereotipos de género en las jóvenes de los ciclos básicos de la unidad académica de ciencias administrativas y humanísticas de la universidad técnica de Cotopaxi, cantón Latacunga, provincia de Cotopaxi, septiembre 2014 –febrero 2015 - Sandoval Cárdenas, Diana Maricela (2015)
The objective of this research is to determine the influence of Facebook on gender stereotyping in young of the basic stages of UTC, Canton Latacunga, Cotopaxi province, period September 2014 _ February 2015. The research is descriptive. The theoretical framework is developed, in which consist issues with scientific basis, based on the criteria of different authors. Also refers to the analysis and interpretation of results of the instrument instruments applied to both students and other persons knowledgeable on the subject; These results are interpreted quantitatively and qualitatively, after which the respective conclusions and recommendations are set….